Capacity Building for Effective Local Governance: Indian Perspectives (International Journal of Food and Nutritional Sciences, 2022)
Local governance is being promoted in India because it is believed that it provides a structural arrangement through which local people and communities can participate in the fight against poverty at close range. However, it is acknowledged that various capacities of a multiplicity of stakeholders and actors need to be strengthened to meet the requirements of effective and responsive local governance. As we know that the most vibrant democratic institution at the grassroots level in India is Panchayati Raj Institutions (PRIs) which is figured to be participatory, accountable, responsive, and transparent and citizen friendly local self-government. The 73rd and 74th Constitutional Amendments provided the constitutional provisions for constructing and operating of such bodies at the local level in India. Some of these provisions are inclusive and democratic in nature such as one-third reservation of seats for women and schedule castes and tribes (dalits) and decentralization of power etc. But the nature of functioning of these bodies for last few years exposed ineffectiveness and inefficiency in governance and delivering of services to the local people. The effective local self-governance indeed is still a distant dream and needs enormous interventions to realize its potential. This dream can possibly be realized by the way of comprehensive understanding of capacity building in terms of governance. The paper discusses a comprehensive meaning of capacity building, issues and challenges related to capacity building for effective local governance in India. It also attempts to view Panchayati Raj Institutions (PRIs) as institutions of local self-governance and not as mere implementers of centrally determined development programs.